If x = 1 and y = -1 , then the value of the expression 6x^2 + 5xy - y^2 is ______
Answers
Answered by
0
Answer:
6x^2+5xy-y^2
=6(1)^2+5(1)(-1)-(-1)^2
Step-by-step explanation:
=6-5-1
=0
Answered by
0
Answer:
0
Step-by-step explanation:
x = 1 and y = -1
6x^2 + 5xy - y^2
= 6(1)^2 + 5(1)(-1) - (-1)^2
= 6 + (-5) + (-1)
= 6 -5 -1
= 1 -1 = 0
Similar questions
English,
2 months ago
India Languages,
2 months ago
Hindi,
5 months ago
Computer Science,
5 months ago
Math,
1 year ago
Computer Science,
1 year ago
Science,
1 year ago